Books are weapons : the Polish opposition press and the overthrow of communism - Doucette, Siobhan (Series in Russian and East European studies., 2017)
Books Are Weapons shows how the independent press, rooted in the long Polish tradition of well-organized resistance to foreign occupation, reshaped this tradition to embrace non-violent civil resistance while creating a network which evolved from a small group of dissidents into a broad opposition movement with cross-national ties and millions of sympathizers. It was the galvanizing force in the resistance to communism and the rebuilding of Poland's democratic society in the 1980s.--